If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(0.5x + 7) = 12 Reorder the terms: 4(7 + 0.5x) = 12 (7 * 4 + 0.5x * 4) = 12 (28 + 2x) = 12 Solving 28 + 2x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + 2x = 12 + -28 Combine like terms: 28 + -28 = 0 0 + 2x = 12 + -28 2x = 12 + -28 Combine like terms: 12 + -28 = -16 2x = -16 Divide each side by '2'. x = -8 Simplifying x = -8
| 3+4=20 | | 12c+14= | | 8z+4-3z=44-3z | | x^4+x^2-14x-8=0 | | x^4+15x^2=0 | | 9x-11=5x+9 | | 20x^2-21x+4.5= | | 2(x+3)=-16 | | 8x-2=20-5x | | (2x+3)(2x+3)=49 | | -5c+3d-3c+8-d= | | -5i(6-4i)= | | 8x-2=10+3x | | (2x+3)2=49 | | 2(3-x)=10-(x+1) | | (7+2i)-(-4-i)= | | 15x^2+10x^2=0 | | x+0.44444444444=0.75 | | x+0.4=0.75 | | 4.25+3.5g=11 | | 4.25x+3.5=11 | | h=38-3t-5t^2 | | y=(9x+5)*4 | | y=9x+5*4 | | 3.25p-81=1.25 | | 3.25+1.25p=81 | | 16x^3+4x^2=0 | | x^2+3y^2-8x+4y-2=0 | | 3.25p+1.25=81 | | 16x^3-4x^2=0 | | 34x+4567=56x-210 | | 34x+4567=56x |